The complete chloroplast genome of Grewia biloba var. parviflora (Bunge) Hand.-Mazz. (Malvaceae) - Wen-Juan Hou; Wen-Xiao Men; Che Bian; Yue-Yue Song; Yan-yun Yang; Liang Xu; Ting-Guo Kang (Mitochondrial DNA. Part B. Resources, 2023)
Grewia biloba var. parviflora (Bunge) Hand.-Mazz. (1933), a shrub or small tree, is native to northern and southern China. It is an excellent relief and medicinal plant. The complete chloroplast genome is 158,043 bp in length, with a large single-copy region of 86,957 bp, a small single-copy region of 20,138 bp, two inverted repeat regions of 25,474 bp each, and a GC content of 37.4%. There were 129 genes annotated, including 84 known protein-coding genes, 37 tRNAs, and eight rRNAs. The phylogenetic trees are constructed using plastome data from 38 species and the maximum-likelihood method. The results of the chloroplast genome-wide analysis and the phylogenetic tree show the taxonomic phylogeny of the G. biloba var. parviflora in relation to other species, increasing the accuracy of the phylogenetic classification of the plant.